1975
DOI: 10.1037/h0076339
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Preference Inventory high point codes versus expressed choices as predictors of college major and career entry.

Abstract: For 151 male bachelor's degree university graduates, expressed choices measured by preferences made as high school seniors on the American College Test Student Profile Section were significantly more accurate predictors of graduating college major and of career entry occupation than were their Vocational Preference Inventory high point codes. There was no relationship between the Vocational Preference Inventory high point codes and the expressed choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Considerable evidence suggests that a person's stated occupational goal is as good as or better than any other available predictor of actual vocational behavior (e.g., Borgen & Seling, 1978;Dolliver, 1969;Gade & Soliah, 1975;Slaney, 1978;Touchton & Magoon, 1977). Therefore, each participant was asked to write a one-line response to the question, What is your career goal?…”
Section: Methodsmentioning
confidence: 99%
“…Considerable evidence suggests that a person's stated occupational goal is as good as or better than any other available predictor of actual vocational behavior (e.g., Borgen & Seling, 1978;Dolliver, 1969;Gade & Soliah, 1975;Slaney, 1978;Touchton & Magoon, 1977). Therefore, each participant was asked to write a one-line response to the question, What is your career goal?…”
Section: Methodsmentioning
confidence: 99%
“…These findings underscore the need to examine the structure of the current labor market as part of the career counseling process. In research with college students it has been found that expressed career choice predicts major at graduation with as much, or more, accuracy than measured interests (Dolliver, 1969;Gade & Soliah, 1975;Holland & Lutz, 1968;Whitney, 1969). Therefore, it seems reasonable to assume that if the level of aspiration for certain careers does not match the number of jobs available, all college graduates will not be able to get jobs that are congruent with their interests and abilities.…”
mentioning
confidence: 99%
“…This is comparable to the results of a study by Gade and Soliah (1975) who found approximately a 50% agreement between VPI high point and expressed preference. Correct classification of expressed preference from policy models increased nearly 100% relative to the VPI.…”
Section: Other Analysessupporting
confidence: 88%